2010
DOI: 10.1118/1.3512796
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale entropy of laser Doppler flowmetry signals in healthy human subjects

Abstract: Multiscale entropy of LDF signals in healthy subjects shows variation with scales. Moreover, as the variation pattern observed appears similar for all the tested signals, multiscale entropy could potentially be a useful stationary signature for LDF signals, which otherwise are probe-position and subject dependent. Further work could now be conducted to evaluate possible diagnostic purposes of the multiscale entropy of LDF signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…The results show a nonmonotonic evolution of the multiscale entropy for the 12 LDF signals. We therefore confirm the results obtained in [11] and show that the singled out scales are similar for signals recorded simultaneously at different locations on a given subject. This also shows that the observed amplitude changes in the LDF signals (amplitude changes due to physiological variations, e.g., modifications in vascular tone) do not influence much the multiscale entropy pattern.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The results show a nonmonotonic evolution of the multiscale entropy for the 12 LDF signals. We therefore confirm the results obtained in [11] and show that the singled out scales are similar for signals recorded simultaneously at different locations on a given subject. This also shows that the observed amplitude changes in the LDF signals (amplitude changes due to physiological variations, e.g., modifications in vascular tone) do not influence much the multiscale entropy pattern.…”
Section: Resultssupporting
confidence: 90%
“…It has been shown that multiscale entropy of HRV data is able to separate healthy and pathologic groups [9], [10]. A very recent study has implemented the first computation of the multiscale entropy for signals of the peripheral CVS (LDF signals) [11]. A nonmonotonic evolution of the multiscale entropy for LDF signals has been reported.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Variations of skin perfusion are easily detected by LSCI and LDF techniques, but a robust interpretation of the information very often necessitates image and/or signal processing works (see, e.g., Refs. [24][25][26]. Moreover, LSCI and LDF skin data coming from the peripheral cardiovascular system, a comparison of the processing results with those obtained from signals of the central cardiovascular system (e.g., HRV signals) can bring interesting information to better understand the dynamics of the whole cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%
“…Complexity is typically assessed as "entropy," a general measure of "disorganization" in physical, chemical and biological phenomena [9]. In biomedical research, entropy is used as a quantitative parameter, and is typically assessed in continuous, but temporally unpredictable, physiological signals, such as electrocardiography [10], electroencephalography [11], blood pressure [12], laser Doppler flowmetry (LDF) [13], and photoplethysmography (PPG) [14]. Physiological signals may be regular (e.g., more periodic) or irregular.…”
Section: Introductionmentioning
confidence: 99%